2006
DOI: 10.1080/01411920600635452
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interactive whiteboards on teacher—pupil interaction in the National Literacy and Numeracy Strategies

Abstract: The study set out to investigate the impact of interactive whiteboards (IWBs) on teacher-pupil interaction at Key Stage 2 in the teaching of literacy and numeracy. As part of the National Literacy and Numeracy Strategies, IWBs have been made widely available as a pedagogic tool for promoting interactive whole class teaching. In order to investigate their impact, the project looked specifically at the interactive styles used by a national sample of primary teachers. A total of 184 lessons were observed over a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 11 publications
2
116
0
8
Order By: Relevance
“…These schools were selected on the basis of existing working relations with the project team, and also schools' expressed interest to be involved in the research. In justification of this sampling method, our aim was not to survey classrooms to describe and offer generalisations of the normal practices with IWBs, nor to evaluate their effectiveness overall (for current evaluations see Smith, Hardman & Higgins, 2006;Moss, 2007). The purpose of this work was to investigate the function and value of IWBs as mediating tools in the communicative process of education through case studies involving microanalysis.…”
Section: Methodsmentioning
confidence: 99%
“…These schools were selected on the basis of existing working relations with the project team, and also schools' expressed interest to be involved in the research. In justification of this sampling method, our aim was not to survey classrooms to describe and offer generalisations of the normal practices with IWBs, nor to evaluate their effectiveness overall (for current evaluations see Smith, Hardman & Higgins, 2006;Moss, 2007). The purpose of this work was to investigate the function and value of IWBs as mediating tools in the communicative process of education through case studies involving microanalysis.…”
Section: Methodsmentioning
confidence: 99%
“…As the class moved at a faster pace, the manner in which class was taught also had a slight shift. As noted in both McNabb & (2000) and in Smith, Hardman, & Higgins (2006) the IWB causes classrooms to tend to be more whole group. The whole group style was positively viewed by most students.…”
Section: Relation Of the Results To Literaturementioning
confidence: 99%
“…Concerning the differentiated learning, study of IWB integration in the UK reported that lessons with IWB are more often dominated by whole-class activities (Smith, Hardman, & Higgins, 2006). Categorizing IWB technology, some authors even use the term "interactive whole-class technologies" (IWCTs) (Beauchamp et al, 2010).…”
Section: Discussionmentioning
confidence: 99%